Submission to Education and Health Standing Committee Inquiry into the Department of Education's Independent Public Schools Initiative - Fitzgerald, Scott; McGrath-Champ, Susan; Wilson, Rachel; Stacey, Meghan; Rainnie, Al; Parding, Karolina (Legislative Assembly, Parliament of Western Australia, 2016)
Over the last five years, with the above colleagues at Curtin University and the University of Sydney, I have examined the changes associated with the Independent Public Schools policy initiative in Western Australia. This research has in part involved comparative policy analysis which has placed the IPS initiative within a broader history of attempts by governments to devolve responsibility and decision making through the establishment of local school ‘autonomy’ or ‘self-managing schools’. Despite a very mixed record of effects, school autonomy has been embraced widely by western nations, including British ‘Academy’ schools, USA ‘Charter’ schools, and a surge of ‘independent’ schools, such as in Sweden. In Australia, such government devolution policies have included Better Schools in Western Australia (1987) Schools Renewal in New South Wales (1989) and Schools of the Future in Victoria (1993). For all the initial discussion of the novelty of the IPS policy, and all its focus on community and school empowerment as opposed to choice, competition and efficiency, the IPS initiative is part of this broader reform agenda to transform public education. In reviewing this experience of the push towards self-managing schools within Australia and internationally we found that what occurs through such policies is a shift of risk to families and an abrogation of responsibility on behalf of government to operate and fund an inclusive and equitable public education system (Fitzgerald and Rainnie 2011; Fitzgerald and Rainnie 2012). As I note below, research has consistently shown, at best, a very tenuous link between school autonomy and improved student outcomes across public education systems.